LFA-1 in T cell priming, differentiation, and effector functions - Gerard, A; AP, Cope; Kemper, C; Alon, R; Kochl, R (Cell Press, 2021)
The integrin LFA-1 is crucial for T cell entry into mammalian lymph nodes and tissues, and for promoting interactions with antigen-presenting cells. However, it is increasingly evident that LFA-1 plays additional key roles beyond the mere support of adhesion between T cells, the endothelium, and/or antigen-presenting cells. These include roles in homotypic T cell: T cell communication, the induction of intracellular complement activity underlying Th1 effector cell polarization, and the support of long-lasting T cell memory. Here, we summarize briefly current knowledge of LFA-1 biology, discuss novel cytoskeletal regulators of LFA-1 functions, and review new aspects of LFA-1 mechanobiology that are relevant to its function in immunological synapses and in specific pathologies arising from LFA-1 dysregulation.